In Vitro Antiviral Potential, Antioxidant, and Chemical Composition of Clove (Syzygium aromaticum) Essential Oil - Manal Jameel Kiki (Molecules, 2023)
Viral infections are spread all around the world. Although there are available therapies, their safety and effectiveness are constrained by their adverse effects and drug resistance. Therefore, new natural antivirals have been used such as essential oils, which are natural products with promising biological activity. Accordingly, the present study aimed to identify the components of clove (Syzygium aromaticum) essential oil (EOCa) and verify its antioxidant and antiviral activity. The oil was analyzed using GC/MS, and the antioxidant capacity was evaluated as a function of the radical scavenging activity. A plaque reduction test was used to measure the antiviral activity against herpes simplex virus (HSV-1), hepatitis A virus (HAV), and an adenovirus. GC/MS analysis confirmed the presence of eugenol as the main component (76.78%). Moreover, EOCa had powerful antioxidant activity with an IC50 of 50 µg/mL. The highest antiviral potential was found against HAV, with a selectivity index (SI) of 14.46, while showing poor selectivity toward HSV-1 with an SI value of 1.44. However, no relevant effect was detected against the adenovirus. The antiviral activity against HAV revealed that its effect was not related to host cytotoxicity. The findings imply that EOCa can be utilized to treat diseases caused by infections and free radicals.